A role for anti‐BP180 autoantibodies in chronic rhinosinusitis. (8th July 2013) - Jeffe, Jill S.; Seshadri, Sudarshan; Hamill, Kevin J.; Huang, Julia He; Carter, Roderick; Suh, Lydia; Hulse, Kathryn E.; Norton, James; Conley, David B.; Chandra, Rakesh K.; Kern, Robert C.; Jones, Jonathan C. R.; et al.
Abstract : Objectives/Hypothesis: Chronic Rhinosinusitis (CRS) is accompanied by evidence of a vigorous adaptive immune response, and emerging studies demonstrate that some nasal polyps manifest a polyclonal autoantibody response. We previously found that antibodies against BP180, a component of the hemidesmosome complex and the dominant epitope in autoimmune bullous pemphigoid, were found at elevated levels in nasal polyp tissue. Given the critical role of hemidesmosomes in maintaining epithelial integrity, we sought to investigate the distribution of BP180 in nasal tissue and evaluate for evidence of systemic autoimmunity against this antigen in CRS. Study Design: Case‐control experimental study. Methods: The expression and distribution of BP180 in cultured nasal epithelial cells and normal nasal tissue were confirmed using real‐time polymerase chain reaction (PCR), Western immunoblotting, immunofluorescence and immunohistochemistry. Sera were collected from three groups: control, CRSsNP, and CRSwNP. A commercially available ELISA was utilized to compare anti‐BP180 autoantibody levels in sera. Results: BP180 is expressed in nasal epithelium, but is not confined to the basement membrane as it is in human skin. In cultured nasal epithelial cells, confocal immunofluorescence showed a punctate distribution of BP180 along the basal surface, consistent with its distribution in epithelial keratinocytes. There are significantly higher levels of circulating nonpathologic anti‐BP180 autoantibodies in CRS patients compared with normal controls ( P <0.05). Conclusions: BP180 is more widely expressed in nasal epithelium versus skin, although it appears to play a similar role in the formation of hemidesmosomes along the basement membrane. Further investigations are ongoing to characterize the pathogenicity of the anti‐epithelial antibody response in CRS. Level of Evidence: N/A. Laryngoscope, 123:2104–2111, 2013